COPYRIGHT EXEMPTION AND APPLICATION OF INFORMATION TECHNOLOGY AS FACTORS INFLUENCING TRANSCRIPTION OF READING MATERIALS FOR THE VISUALLY IMPAIRED IN NIGERIA (2012)
The transcription and distribution of reading materials to the visually impaired have remained grossly inadequate relative to their information need, and access. Studies have shown that the low transcription and distribution of reading materials for the visually impaired in Nigeria is as a result of poor funding, Braille literacy and reading interest. Unfortunately, copyright exemption and information technology for the visually impaired have been neglected. The study, therefore, investigated copyright exemption and the application of information technology as factors influencing the transcription of reading materials for the visually impaired in Nigeria. The study adopted survey research design of the ex-post facto type. Total enumeration technique was used to select 470 personnel in libraries (24), secondary schools (347), tertiary institutions (41) and non-governmental organizations (58) concerned with transcription of reading materials into alternative format in Nigeria. This included nine institutions that served as participants in the interview. Four instruments (Knowledge of Exemption Scale (?= 0. 78), Information Technology Use Scale (?= 0. 74), Transcription of Reading Materials Scale (?= 0.76) and an interview schedule were used. Six research questions were answered and three null hypotheses were tested at 0.05 level of significance. Data were subjected to descriptive statistics, Pearson Product Moment Correlation, Multiple Regression and content analysis. Transcribers, libraries and schools for the visually impaired had high knowledge of copyright exemption (70.8%); information technology application in transcription was low (7.4%) while information needs (66.8%) and curriculum specification (63.4%) were the major criteria for selection of material for transcription. Eighteen different types of equipment were used for transcription. Formal collaboration existed among transcribers and providers of alternative formats. Shortage of transcribers (87.5%), lack of software and equipment (81%) and high cost of production (77.6%) were the major problems of transcription of reading materials. There was a significant positive relationship between copyright exemption and transcription of information materials into alternative format (r=0.741,p<0.05). A significant positive relationship existed between application of information technology and transcription of information material (r=0.62: p<0.05). Copyright exemption and application of information technology had joint positive influence on transcription of reading material F(2,469) =416.7; p< 0.05). The interview revealed a high knowledge of copyright exemption and low use of information technology among transcribers. It also showed that transcribers were of the opinion that IT tools were expensive to procure but crucial to improving transcription. Copyright exemption and information technology application are crucial factors in effective transcription of reading materials into alternative formats and the provision of information services to the visually impaired. Enrichment programmes geared towards increased application of copyright exemption and information technology for all institutions involved in transcription were suggested.